OPTIMAL PORTFOLIO SELECTION FOR A DEVELOPMENT BANK (Journal of Economic Research & Business Administration, 2018)
This paper examines the formation and optimization of the investment portfolio of the development bank, which implements the state policy of financing socially significant projects that contribute to the economic growth of the country. This model takes into account the bank’s objectives and risk attitude.We propose a methodology for forming an optimal portfolio based on the Markowitz theory. An important feature of the proposed methodology is that it takes into account differences in priorities of the development bank and commercial banks. In particular, the development bank is less interested in maximizing profits and is more interested in developing products and industries with high value added. The main focus of our methodology is on practical implementation issues arising because of data availability constraints existing for Kazakh companies. With that focus in mind, we model the portfolio optimization problem for the development bank that invests a limited amount of funds in private companies from various sectors of Kazakhstan’s economy. To make this example as useful as possible for the practical activities of Kazakhstan financial institutions, we use real yield data for large Kazakhstani companies listed on the Kazakhstan Stock Exchange.